Descriptive of Critical Thinking in Nursing Care of Nurses: A Survey Study - Arruum, Diah; Suza, Dewi Elizadiani; Asiah, Nur; Sitepu, Nunung Febriany (Universitas Prima Indonesia, 2025)
Nurses are responsible for providing nursing care to patients while being treated in the hospital. Providing nursing care to patients requires critical thinking skills for nurses to be able to achieve various problem-solving and decision-making in care so that the needs and treatment process of patients can be met. Critical thinking in nursing care begins with the assessment to the evaluation of nursing care for patients. However, obstacles in critical thinking in nursing care are still a concern for nurses. This study aims to descriptive of critical thingking in nursing care of nurses. This study is a descriptive survey study with a cross-sectional design. This study involved 69 nurses. This study was conducted in September-December 2019 in Medan. The sample was selected using the purposive sampling method, and data were collected through a questionnaire developed by the researcher related to critical thinking in nursing care. The output of data analysis uses frequency distribution. The results obtained were that the age range of nurses was 20-30 years with female gender, educated as professional nurses, and the longest work period was 1-4 years; the majority of career levels were level I. The critical thinking ability of nurses in the capable category was 92.7%. The majority of nurses have good critical thinking knowledge in nursing care for patients. Nurses who have good nursing care reflect good competence and performance. Nursing managers need to motivate and monitor nurses continuously in nursing care to patients because critical thinking affects the caring behavior of nurses. Nurses who have good critical thinking can improve performance in providing nursing care.